Separation of Ferronickel Nugget from Limonitic Laterite Ore Using Self-reduction - Ju, Pyongsu; Ryom, Kwangchol; Hong, Kumdong (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
To efficiently extract nickel from low grade limonitic laterite ore, a separation method of  ferronickel nugget by self-reduction of coal composite limonitic laterite ore briquette was investigated. In this investigation, in order to decrease the separation temperature of ferronickel nugget, the selective reduction by control of coal mixing rate was introduced, reductant blended in briquette was inadequate for the reduction of nickel and iron. In the reduction process nickel was preferentially reduced, while iron was partially reduced due to inadequate amount of reductant. After reduction, a certain amount of FeO existed in the briquette, this residual FeO had a great role in the formation of low melting point slag, which could facilitate the formation and the separation of ferronickel nugget at relatively low temperature. In this investigation, the reduction experiments were all conducted at 1300°C. To evaluate the formation and the separation of ferronickel nugget in reduction process, reduced products were observed in outside under various coal mixing rate (C/O), CaO mixing rate and holding time. And then the effect of C/O and CaO mixing rate on nickel content of ferronickel nugget and nickel recovery ratio were investigated. The results showed that C/O of 7%, CaO mixing rate of 8% and holding time of 40min were suitable for the separation of ferronickel nugget from limonitic laterite ore. Nickel and iron content of ferronickel nugget and nickel recovery ratio were 4.75%, 89.51% and 85%, respectively. Ferronickel nuggets were easily separated from slag by crushing and sieving. This separation method can indicate one innovative process for pyrometallurgical utilization of low grade limonitic laterite ore.